BIOLOGI REPRODUKSI BUNGA Cassine koordersii Kostermans (Celastraceae) KOLEKSI KEBUN RAYA BOGOR - Ardhianto, D.; Sari, Rismita; Djalil, A. (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2009)
A study on flower biology of Cassine koordersii Kostermans was carried out in the Bogor Botanic Garden on April â November 2002. The plant produces flowers in umbel inflorescences that open sequentially, starting from the lowest branch of the inflorescence. There is no spatial separation between the anther and the stigma, and the dispersal of highly viable pollen takes place within the period of stigma receptivity. The flowers also show some characters of entomophily. Visitor insects are flies (ordo Diptera, family Syrphidae and Tachinidae) and ants (ordo Hymenoptera, family Formicidae). In general, the morphological and phenological characteristics of the flower allow self pollination to occur successfully. Floral assessment using Crudens Outcrossing Index showed that the flower is self-compatible.